Dissociation of reward and effort sensitivity in methcathinone-induced Parkinsonism - Chong, T; Bonnelle, V; Veromann, K; Juurmaa, J; Taba, P; Plant, O; Husain, M (Wiley, 2017)
Methcathinone-induced Parkinsonism is a recently described extrapyramidal syndrome characterized by globus pallidus and substantia nigra lesions, which provides a unique model of basal ganglia dysfunction. We assessed motivated behaviour in this condition using a novel cost-benefit decision-making task, in which participants decided whether it was worth investing effort for reward. Patients showed a dissociation between reward and effort sensitivity, such that pallidonigral complex dysfunction caused them to become less sensitive to rewards, while normal sensitivity to effort costs was maintained.